2011
DOI: 10.1080/10550887.2011.581988
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Sexual Harassment and Generalized Harassment in the Workplace Over Ten Years: Effects on Deleterious Drinking Outcomes

Abstract: While harassment in the workplace has been linked to deleterious drinking outcomes, researchers have yet to examine the long-term effects of chronic workplace harassment. During a ten year longitudinal mail survey, university employees (N = 2265) were administered measures of sexual harassment, generalized workplace harassment, and problematic drinking. Using growth mixture modeling, two latent classes of workplace harassment emerged: infrequent and chronic. Demographic characteristics (gender, age, and race) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 56 publications
6
26
2
Order By: Relevance
“…There were no reciprocal relations involving binge drinking, which was surprising considered past research finding relations between SH and binge drinking among adults (e.g., McGinley, Richman, & Rospenda, 2011; Richman et al, 1999). Perhaps binge drinking is so common among college students that associations with specific risk factors like SH are diluted by the stronger risk factor of merely being in college.…”
Section: Discussioncontrasting
confidence: 64%
“…There were no reciprocal relations involving binge drinking, which was surprising considered past research finding relations between SH and binge drinking among adults (e.g., McGinley, Richman, & Rospenda, 2011; Richman et al, 1999). Perhaps binge drinking is so common among college students that associations with specific risk factors like SH are diluted by the stronger risk factor of merely being in college.…”
Section: Discussioncontrasting
confidence: 64%
“…Research on SH and gender has been mixed. While several studies have reported that women experience greater mean levels of SH than men (Berdahl and Moore, 2006; Das, 2009; Hand and Sanchez, 2000; Kalof et al, 2001; Lott et al, 1982; Reilly et al, 1986), others have reported more nuanced (McGinley et al, 2011), nonsignificant (Rospenda et al, 2000), or reversed (McMaster et al, 2002; Petersen and Hyde, 2009a,b; Wei and Chen, 2012) links between gender and SH. Still, studies have shown that some women are especially stressed or prone to self-blame by this form of victimization, which may have implications on their mental health (Goldstein et al, 2007; Lott et al, 1982; Petersen and Hyde, 2013a, 2013b; Till, 1980; Yoon et al, 2010), although few studies have attempted to understand these relations longitudinally in a young adult collegiate sample.…”
Section: Examinations Of Sh Over Timementioning
confidence: 99%
“…Studies using advanced longitudinal data analytic techniques have also established the existence of chronic SH in adult workers. Using latent growth mixture modeling, McGinley et al (2011) uncovered two trajectories of SH: infrequent and chronic. Workers experiencing chronic SH consistently experienced elevated levels of SH over 10 years, and these chronic victimization experiences in turn predicted a battery of alcohol use outcomes.…”
Section: Examinations Of Sh Over Timementioning
confidence: 99%
See 2 more Smart Citations